Encounters between social work and STS - Andersen, Lars Bo; Hoffmann Birk, Rasmus (STS Encounters, 2018)
From the introduction: This special issue was motivated by a series of productive ‘encounters’ between a diverse group of researchers and practitioners working in and between the fields of social work and STS - most notably the ‘Introducing STS and Social Work’ sessions at the Danish STS conference in 2016.